How accessible is IB schooling? Evidence from Australia. (April 2017) - Dickson, Anisah; Perry, Laura B.; Ledger, Susan
This study examines access to International Baccalaureate schools in Australia. It is important to examine whether, as a highly regarded form of rigorous academic education, IB programmes are available to a wide range of students. We examine the location of schools in Australia that offer one or more of the IB Primary Years Programme, Middle Years Programme or Diploma Programme, their fees and admissions policies, and what types of students they enrol. The findings show that most schools in Australia that offer any of these three IB programmes are located in affluent communities of large cities, are privately-funded, charge moderate to high fees, and enrol mostly students from privileged socioeconomic backgrounds.